2008
DOI: 10.1582/leukos.2007.004.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Acceptance of Demand-Responsive Lighting in Offices with and without Daylight

Abstract: Participants (N ϭ 33) in an office laboratory were exposed to an initial baseline electric lighting level of 400 lx on the desktop. The electric lighting was dimmed smoothly over 10 seconds. During the dim, and for 30 seconds afterwards, the participant performed a computer-based proofreading task. The participants indicated if they had noticed the change, and whether the lighting conditions were acceptable. This was repeated over multiple trials, with dimming from 0 to 80 percent, and with or without dayligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…Half of participants detected a 15% change and accepted a 20%-30% reduction [22] • Occupants noticed a 20% change without any daylight, a 40%-60% change with daylight, and an 80% change with strong daylight [23].…”
Section: % Of Participants Detected Light Level Changes Of 15%-20% mentioning
confidence: 99%
“…Half of participants detected a 15% change and accepted a 20%-30% reduction [22] • Occupants noticed a 20% change without any daylight, a 40%-60% change with daylight, and an 80% change with strong daylight [23].…”
Section: % Of Participants Detected Light Level Changes Of 15%-20% mentioning
confidence: 99%
“…In integrated design, daylight works as a mediating factor in the perception of light fading. A study by Newsham et al (2008) surveyed 39 individuals who underwent 42 different trials in private daylit mock-up offices, while performing computer-based tasks under various daylight conditions. The electric lighting was set to full output at the start of the trial, and then dimmed down to the target of 400 lux.…”
Section: Lighting Control Settings and Occupant-centred Adapationmentioning
confidence: 99%
“…The study confirmed that a reduction of 20% illuminance -provided, in this case, by a mix of daylight and electric lighting -is unlikely to be noticed. However, with high daylight provision, this 20% actually corresponds to up to 60% of dimming down of electric lighting (Newsham et al, 2008).…”
Section: Lighting Control Settings and Occupant-centred Adapationmentioning
confidence: 99%
See 1 more Smart Citation
“…Newsham et al performed a follow-up study that did include daylight. 8 In the experiment, they dimmed lighting down from the baseline of 400 lx with 0%, 20%, 40%, 60% and 80%, all in 10 seconds. They showed that in situations with no daylight, the artificial lighting can be dimmed down by 20% without occupants noticing the change and dimmed down by 40% to still be perceived as acceptable.…”
Section: Introductionmentioning
confidence: 99%